Impact of trade liberalisation on manufacturing firms in Jamaica and Trinidad and Tobago - Prescott, La Shaun ([Caribbean Centre for Monetary Studies] [St. Augustine]TT, 2002)
Makes a comparative analysis of the effects of trade liberalization on selected manufacturing firms in Trinidad and Tobago and Jamaica.